Successive and Segmented Watermarking Techniques Based on DWT-SVD and Artificial Bee Colony Algorithm - Ananth, C; Karthikeyan, M (International Journal of Computer Sciences and Engineering, 2025)
Multiple watermarks is to convey multiple sets of information designed to suit differing objectives and is used to increase robustness and security with many different methods in which the embedded information is not easily lost. DWT-SVD based successive and segmented watermarking technique is proposed using Artificial Bee Colony Algorithm (ABC). The understanding between the transparency and robustness is considered as an optimization problem and is removed by applying the ABC algorithm. This algorithm is used to obtain the highest possible robustness without losing the transparency. The successive and segmented of multiple watermarking techniques makes the watermarks much more robust to more attacks. The optimization on successive and segmented watermarking achieves more imperceptibility and robustness.